Desejos comodificados : dos classificados aos perfis nos aplicativos na busca por parceiros do mesmo sexo - Silva, João Paulo Ferreira da (2017)
This research investigated the criteria that were used in the search for loving and/or sexual partners between men in two different periods: (a) by the Lampião da Esquina newspaper that was in circulation before the break out of the HIV-AIDS epidemic and the advent of the Internet (b) after the epidemic and expansion of the commercial Internet through the Hornet® web application. Therefore, the research was established at two certain moments: (1) through the Lampião da Esquina newspaper, circulated in Brazil when censorship was relaxed by the military regime in the sections "troca-troca" (partner swapping) and “cartas na mesa” ("cards on the table" similar to an advice column) from April, 1978 to June, 1981 and (2) based on an analysis of the profiles currently sought by the Hornet® web application, which had ages and residence equivalent to those found in the newspaper advertisements. As a specific aim, we analysed what changed in terms of loving, sexual and personal expectations among men who sought other men; how the search for loving and/or sexual partners began to affect desires, market, work, leisure and forms of subjectivation with new collective ideas. To do this, we investigated the following considering descriptions published in the respective sections (a) and web application (b), the intersected cleavages in the search (race, ethnicity, generation, social class, education and location), as well as the processes, mediations, break-ups and dilemmas that modulated loving and sexual expectations, above all, by the centrality of sex appeal and body as elements imbued by emerging socioeconomic and cultural characteristics. The research presents a multi-method design and therefore combines quantitative and qualitative techniques using documentary analysis and online profiles, integrating statistical controls using the SPSS package. In order to construct the theoretical reflection intended, references were made to digital media, gender and sexuality. From the results, the research allowed to recognize a process of intensification of the selection of partners from the second moment, keeping continuities and ruptures in relation to the descriptors of the first moment, as well as the emergence of a grammar of the desire that alludes to the sexual panic of AIDS in sociological terms.